2013
DOI: 10.1016/j.parkreldis.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Motor phenotype and magnetic resonance measures of basal ganglia iron levels in Parkinson's disease

Abstract: BackgroundIn Parkinson's disease the degree of motor impairment can be classified with respect to tremor dominant and akinetic rigid features. While tremor dominance and akinetic rigidity might represent two ends of a continuum rather than discrete entities, it would be important to have non-invasive markers of any biological differences between them in vivo, to assess disease trajectories and response to treatment, as well as providing insights into the underlying mechanisms contributing to heterogeneity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…During healthy aging, qT2* (a quantitative MRI parameter related to qT2) has also been found to be negatively correlated with age in a wide range of brain areas, in particular in bilateral putamen, reflecting an increased level of iron [32]. In parkinson's disease, lower qT2* in putamen is also associated with more severe motor symptoms [33]. In addition, we have shown that qT1 parameters were decreased in the left caudate nucleus by 68 % with DLB.…”
Section: Discussionmentioning
confidence: 99%
“…During healthy aging, qT2* (a quantitative MRI parameter related to qT2) has also been found to be negatively correlated with age in a wide range of brain areas, in particular in bilateral putamen, reflecting an increased level of iron [32]. In parkinson's disease, lower qT2* in putamen is also associated with more severe motor symptoms [33]. In addition, we have shown that qT1 parameters were decreased in the left caudate nucleus by 68 % with DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Since aging is the major risk factor for many neurodegenerative diseases, agerelated accumulation of iron may be an important factor that contributes to neurodegenerative pathology (Ward et al, 2014). This notion has been supported by post mortem and in vivo human studies identifying abnormal iron deposition in neurodegenerative diseases such as Alzheimer's disease (AD) (Cornett et al, 1998;Bartzokis et al, 2000) and Parkinson's disease (PD) (Bartzokis et al, 1999;Bunzeck et al, 2013;Sofic et al, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Over a 3-year follow-up, increased R2* in the substantia nigra correlated with the worsening of motor symptoms of PD, suggesting that R2* may be a biomarker of disease progression in PD (Ulla et al, 2013). Association between high R2* signal and LIDs has yielded inconsistent results either showing a positive (Bunzeck et al, 2013) or no correlations (Wieler, Gee, & Martin, 2015) between iron deposition and motor complications. Early-onset PD patients showed a higher field-dependent R2 increases in the substantia nigra, putamen, and pallidum, which decreases as the disease progresses, suggesting that dysregulation of iron metabolism occurs in PD (Bartzokis et al, 1999).…”
Section: Iron Deposition and Neuromelaninmentioning
confidence: 99%